Anthropogenic Decline of Ecosystem Services Threatens the Integrity of the Unique Hyrcanian (Caspian) Forests in Northern Iran - Zarandian, A.; Baral, H.; Yavari, A.R.; Jafari, H.R.; Stork, N.E.; Ling, M.A.; Amirnejad, H. (MDPI, 2016)
The unique Hyrcanian (Caspian) forests of northern Iran provide vital ecosystem services for local and global communities. We assess the status and trends of key ecosystem services in this region where native forest conversion has accelerated to make way for housing and farm development. This is a mountainous forested area that is valuable for both conservation and multiple human uses including recreation and farming. It contains globally significant natural habitats for in situ conservation of biological diversity. A rapid, qualitative, and participatory approach was used including interviews with local households and experts in combination with assessment of land use/cover remote sensing data to identify and map priority ecosystem services in the Geographic Information System (GIS). Based on the interests of the beneficiaries, eight priority services (food production, water supply, raw materials, soil conservation, water regulation, climate regulation, biodiversity, and recreation) were identified and mapped. The results indicate the current typical spatial distribution of the provided services based on structural characteristics of the study landscape and their changing trends through a comparison of past, present and future land use, and land cover. Although food production and recreation have greatly increased in recent decades, the other services, in particular timber production, biodiversity, and water purification and supply are being gradually lost. The results of this study and of others elsewhere should raise awareness of ecosystem service status and trends and the value of examining these since they provide much of the information to inform natural resources policy and decision making. The declines in supply of key ecosystem services both within and outside the protected area are creating conflicts within communities as well as impacting on the integrity of the area and careful planning and conservation is required to provide win-win opportunities.